Лепные котлы Самосдельского городища и проблема их этнической интерпретации - Попов, П.В. (Степи Европы в эпоху средневековья, 2009)
During exploration at Samosdelka hillfort located in the lower Volga reaches, a complex of modelled cauldrons was singled out. The forms originate from the finds of medieval Turkic-speaking nomads of Central Asia. The forms similar to those used in the pottery of the monuments of the region of the Seven Rivers, should be specially noted. In this region the similar forms have precise dating: the 7th - 8th centuries. On Samosdelka hillfort they should be dated to the 9th I0th centuries. These forms may serve as chronoindicators. thus their distinguishing is of great importance. Generally, the complex under examination should be related with the tribes that composed the Oguz confederation. The appearance of the considerable amount of tableware typical of the nomads in the hillfort collection is a sign of the process of the nomads' transition to settled life. However, the adverse natural climatic conditions of the lower Volga reaches did not permit the formation of the powerful center of settled agricultural culture here. Accordingly, cattle breeding played a great role in the economy of the population of the monument, which caused preservation of nomadic economy. The nomads used Samosdelka hillfort as a place of winter stay.